Religion and HIV Risk Among Male Market Vendors in Kazakhstan - Shaw, Stacey A. (Journal of religion and health, 2020)
This study examines associations between religion and sexual HIV risk among 1342 male migrant and non-migrant market vendors in Kazakhstan. In the multivariate analysis, religious influence was associated with a lower likelihood of having multiple partners. Regular attendance was associated with a lower likelihood of having anal sex with a male partner, but with increased likelihood of having multiple partners. Spending time socially with friends at a mosque or church was associated with lower risk of anal sex with a male partner and lower risk of unprotected sex.